Modulating Osteoclast Activity and Immune Responses with Ultra-Low-Dose Silver Nanoparticle-Loaded TiO2 Nanotubes for Osteoporotic Bone Regeneration - Zhen Wang; Penghui Xiang; Zhe Xu; Meiqi Gu; Rui Zhang; Yifei Li; Fei Xin; Chengla Yi (Journal of Functional Biomaterials)
Introduction: Osteoporosis results from the dysregulation of osteoclast activation mechanisms. The subsequent inflammation in osteoporotic environments further hampers bone healing and impedes osseointegration. Therefore, developing treatments that can modulate osteoclast activity and regulate immune responses is essential for effectively treating osteoporotic bone defects. Methods: In this study, silver nanoparticle-decorated TiO2 nanotubes (Ag@TiO2-NTs) were synthesized through an electrochemical anodization technique for surface modification. The morphology and elemental composition of the Ag@TiO2-NTs structures were characterized using scanning electron microscopy (SEM) and related methods. Subsequently, a series of in vitro and in vivo experiments were conducted to investigate the regenerative potential of Ag@TiO2-NTs in osteoporotic bone defects. In vitro assays focused on evaluating cell viability and osteoclast function, while in vivo assessments employed osteoporotic rat models to monitor bone healing via histological examination and micro-computed tomography (micro-CT) imaging. Results: Our results demonstrated that Ag@TiO2, through the controlled release of trace amounts of silver ions, significantly suppressed osteoclast activity and consequently alleviated bone resorption under osteoporotic conditions. In addition, Ag@TiO2-NTs facilitated the polarization of macrophages toward the M2 phenotype. These biological effects were associated with the stimulation of autophagy, a fundamental mechanism involved in cellular repair. Moreover, the activation of autophagy contributed to the suppression of RANKL-induced NF-κB signaling, a pathway essential for the regulation of bone metabolism Conclusion: These results suggest that this surface modification strategy has the potential to be an ideal implant biomaterial for treating osteoporotic bone defects and a promising strategy for future implant surgeries.